Simulasi Reaksi Kimia Berbasis Algoritma Titrasi Menggunakan Python: Studi Kasus Reaksi Asam-Basa - Czidni Sika Azkia; Claudia Shinta Octa Wibowo; Ayu Puspa Wirani (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2026)
Learning acid–base titration concepts in schools is often constrained by limited laboratory facilities, making interactive and accessible digital simulations an effective alternative. This study aims to develop an acid–base titration simulation based on Python algorithms as an innovative learning medium. The simulation focuses on the reaction between a strong acid (HCl) and a strong base (NaOH) with predetermined volume and concentration parameters, displaying pH changes through a titration curve. The research method applies an algorithmic approach based on stoichiometric calculations, visualized using the Matplotlib library. The simulation results show that the model accurately represents pH changes from acidic conditions to the equivalent point and continues toward basic conditions, consistent with analytical chemistry theory. Validation was conducted through theoretical comparison, visualization against literature curves, and expert evaluation, resulting in an average score of 3.79 out of 4. This indicates that simulation is highly feasible for use in learning. The Python-based simulation not only enhances understanding of titration concepts but also serves as an alternative learning solution in schools with limited laboratory resources.